PENGGARUH LATIHAN QUICK LEAP TERHADAP DAYA LEDAK OTOT TUNGKAI (EXPLOSIVE POWER) PEMAIN BOLA VOLI PUTRA PESANTREN TEKNOLOGI RIAU - Fajar Imam Sanyaja; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstark: The problem in this research is that when striking the ball it seems less like jumping. And when jumping is often not optimal due to weak leg muscle power, so opponents can easily find points when the conditions in the boarding school are from Riau volleyball players for men's technology. The title in this research is "the effect of rapid jump training on volleyball players in Riau pesantren technology" so that the goals of future athletes can perform and play much better and especially after research and discover whether there is an increase in the ability of athletes in volleyball strength to keep track of the opponent's game and to achieve maximum results in the future. The form of this research is to use a one-group pretest-post-test design approach with a population of male volleyball players in Riau pesantren technology. The data in this research is a whole population of 8 people. The instrument used in this study was to use a vertical power jump test, which aims to determine the effect of rapid jump training on the explosive power of leg muscles in the men's volleyball boarding school. The data is then statistically processed to test the normality using the Lilifour test at a significant level of 0.05 α. X LoMax produces 0.182 and Ltable 0.271 based on the analysis of normality test data, which means LoMax <Ltable. while the Y variable yields a LoMax of 0.166 and an Ltable of 0.285. This means LoMax <LTable, then the data is distributed normally. The proposed hypothesis is that there is an effect of rapid jump training on the explosive power of leg muscles in volleyball players in Riau boarding school technology. Based on statistical data analysis, there is an average variable X 16.87 and an average variable Y of 17.26. Thus it can be concluded that for the effect of variable x with variable y the value of t = 3,250 is obtained, then tcount> ttable (3,250)> (1,895), then Ha is accepted, in other words, there is a significant effect on the effect of rapid jump training on male explosive power Riau pesantren technology volleyball players.Key Words: Fast Quick Leap, Leg Muscle Power